LncRNA MNX1-AS1 Contributes to Laryngeal Squamous Cell Carcinoma Growth and Migration by Regulating mir-744-5p/bcl9/β-Catenin Axis. (1st April 2021) - Ma, Bingliang; Ren, Gang; Xu, Jue; Yin, Chenyi; Shi, Yuye
Increasing evidence has indicated that long noncoding RNAs (lncRNAs) are involved in the progression of laryngeal squamous cell carcinoma (LSCC). Here, we aimed to disclose the role of MNX1-AS1 in LSCC progression, and explore whether MNX1-AS1 participates in LSCC progression via targeting miR-744-5p to active BCL9/β-catenin signaling. Sixty-five human LSCC tissues and the paracancerous normal tissues were recruited to determine the levels of MNX1-AS1, miR-744-5p and BCL9 using qRT-PCR. The interaction of miR-744-5p and MNX1-AS1/BCL9 was determined by using the RNA immunoprecipitation (RIP) assay and/or luciferase gene reporter assay. Cell viability, in vivo tumor formation, invasion and migration abilities were detected by MTT, Xenograft models and Transwell assays. MNX1-AS1 level was increased significantly in human LSCC tissues as compared with the normal tissues, which showed a positive correlation with BCL9 level while a negative correlation with miR-744-5p level. High level of MNX1-AS1 predicted a poor prognosis and an advanced clinical process in LSCC patients. miR-744-5p targeted upregulation weakened the luciferase activity of MNX1-AS1 and /BCL9, and downregulated their expression levels-wt, while showed no effect when the binding sites were mutated. Knockdown of MNX1-AS1 markedly weakened cell viability, migration, and invasion abilities, while BCL9 overexpression abolished these tendencies. In addition, MNX1-AS1 downregulation induced decreases in tumor volumes and weights in vivo, accompanied by reductions in BCL9, Ki-67 and β-catenin expression and an increase in miR-744-5p expression. Collectively, this study reveals that MNX1-AS1 contributes to cell growth and migration by regulating miR-744-5p/BCL9/β-catenin axis in LSCC.